Pengaruh Garam-Garam Nitrat Terhadap Konsentrasi Miselisasi Kritis (CMC, Critical Micellization Concentration) Saponin - Amran, Ali (Lembaga Penelitian Universitas Negeri Padang, 2008)
Effect of nitrate salts [NaNO3, KNO3, Mg(NO3)2 and Sr(NO3)2], on the critical micellization concentration (cmc) of saponin, as a natural non-ionic surfactant, which isolated from Sapindus Rarak D.C, have been conducted by a tensiometric method. Results showed that (1) the higher of concentration of the added nitrate salts, the lower cmc reached; (2) the more electropositive of added cation of added salts, the lower cmc reached; (3) the salt effect on the decreasing of cmc and cations binding to micelles becomes more pronounced in the order Na+< K+< Mg2+< Sr2+; and (4) cmc decreasing of nitrat salts Na, K, Mg, dan Sr. were favorable enough, while nitrate salts of Mg and Sr at concentration of ≥ 0,06M, showed a constant decreasing cmc relatively. Key Words: garam-garam nitrat [NaNO3, KNO3, Mg(NO3)2 dan Sr(NO3)2], cmc, serta saponin.